GENERATION Z’s INTEREST IN ISLAMIC MOBILE BANKING: A STUDY ON THE BYOND BY BSI APPLICATION - Fadhilah Nurul Anisa; Ragil Satria Wicaksana; Farah Nur Syafi’ah Wijayanti; Ratih Purbowisanti (Magister Manajemen Universitas Islam Malang, 2025)
This study examines the influence of sharia service quality and technological ease of use on the interest in using the BYOND by BSI application, with customer satisfaction as a moderating variable. Employing a quantitative approach with purposive sampling, the research involved 120 Generation Z customers of Bank Syariah Indonesia in Yogyakarta. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Findings reveal that both sharia service quality and ease of use significantly and positively affect user interest in the application. Customer satisfaction also has a positive impact on interest. However, satisfaction does not moderate the relationship between the independent variables and user interest. This indicates that satisfaction neither strengthens nor weakens the effect of service quality and ease of use on user interest. The results suggest that for Generation Z users of Islamic mobile banking, ease of use and adherence to sharia principles are primary determinants of interest, regardless of satisfaction levels. Therefore, mobile banking development should emphasize user convenience and the consistent integration of Islamic features. Future research is encouraged to explore additional variables such as perception, security, and trust as potential mediators or moderators, and to expand the respondent base beyond Yogyakarta with a larger sample size